Shang-Chi. Volume 2, Shang-Chi vs. the Marvel Universe - Yang, Gene Luen (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment LLC, 2021)
"The martial arts master and his family are back--and this time, they're colliding head-to-head with Earth's biggest and best heroes! Shang-Chi has finally taken his place as the leader of the Five Weapons Society. But using a secret evil organization as a force for good won't be easy. And it's about to get a lot harder when Shang-Chi's fellow super heroes--including the amazing Spider-Man--start to see him as the bad guy!"--